Intra-disciplinary Variations in Academic Interaction: An EAP Study of Environmental Chemistry and Environmental Sustainability Assessed Writing - Ali, Nauman Al Amin; Alhassan, Awad Ahmed (Advances in Social Sciences Research Journal, 2019)
Contemporary accounts of academic discourse increasingly stress the interactive nature of knowledge construction. The conception of science as an irrefutable, objective and reliable representation of Nature, not requiring human mediation, is now largely superseded. Consequently, for readers to bestow their ratification of propositions, writers have to show their deference to the discourse community, meticulously measuring the veracity of their claims, tapping the disciplinary heritage and displaying appropriate appraisal of their status as researchers. Equally, they must create bonds with their readers, explicitly addressing them as peers and interlocutors and appealing to disciplinary schemata. Utilizing a slightly modified version of Hyland’s (2005) typology of academic interaction, this study explores patterns of stance and engagement within the discipline of Environmental Sciences. The intra- disciplinary corpus comprises 16 Ph.D. theses written by Sudanese scholars, 8 of which representing Environmental Sustainability and the other half Environmental Chemistry. Overall results indicate that pervasive interaction in Environmental Sciences is largely dictated by the discursive nature of the field as embodied in the high densities of evaluative and affective markers, though some categories such as the employment of the first pronoun were intentionally shunned. More significantly, statistically significant variations were found between the two subfields, with Environmental Sustainability deploying more intertextual ties, attitudinal markers and alignment with readers. It is argued that the disciplinary synergy characterizing Environmental Sustainability is a contributing factor. On the other hand, the empirical nature of Environmental Chemistry is more manifest in the subtle subcategories of such features as hedging, citation and directives. This is balanced by the more socially- oriented strands of the subfield that render Environmental Chemistry disciplinarily ambivalent. The implications for teaching academic discourse within the post-graduate scene in Sudan are discussed.